2022
DOI: 10.1111/hex.13527
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the obesity concerns of British Pakistani women living in deprived inner‐city areas: A qualitative study

Abstract: Introduction: British South Asians have a higher prevalence of overweight and obesity than the wider population. Bradford (UK), with its high Pakistani presence and levels of economic deprivation, has exceptionally high instances, especially in deprived areas where many Pakistanis reside. British Pakistani women in Bradford are more likely to be overweight and obese. There is uncertainty on how these women can be aided to manage their weight. Therefore, the objective of this study was to explore the obesity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…The finding that Pakistani women did not attend physical activity facilities due to their lack of cultural appropriateness is in line with previous literature (Iqbal et al, 2022 ). According to Jepson et al ( 2012 ), swimming and using the gym are two of the most popular activities for UK residents, but many South Asian women report cultural barriers which means that they are unable to make use of them.…”
Section: Discussionsupporting
confidence: 92%
“…The finding that Pakistani women did not attend physical activity facilities due to their lack of cultural appropriateness is in line with previous literature (Iqbal et al, 2022 ). According to Jepson et al ( 2012 ), swimming and using the gym are two of the most popular activities for UK residents, but many South Asian women report cultural barriers which means that they are unable to make use of them.…”
Section: Discussionsupporting
confidence: 92%
“…Lack of cultural understanding by program providers has been highlighted as a barrier to engagement in a qualitative study 39 in which Pakistani women described their obesity‐related concerns. This study reported barriers such as lack of practical, culturally appropriate dietary advice and health professionals giving contradictory advice due to the lack of cultural awareness of foods consumed 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Lack of cultural understanding by program providers has been highlighted as a barrier to engagement in a qualitative study 39 in which Pakistani women described their obesity‐related concerns. This study reported barriers such as lack of practical, culturally appropriate dietary advice and health professionals giving contradictory advice due to the lack of cultural awareness of foods consumed 39 . Conversely, an example of good practice in a diabetes education intervention targeting health promotion in a UK South Asian population is reported by Gill et al 40 The intervention embedded health ambassadors and provided educational sessions with bilingual professionals in settings which were culturally appropriate such as mosques, resulting in positive learning 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation